First record and potential biocontrol implication of Beauveria bassiana infecting Lema yerburyi on Vanda tricolor from Bali, Indonesia - I PUTU SUDIARTA; DEWA AYU PUTU KANIANITA SANJAYA; SHAH MAHAPATI DINARKAYA; GUSTI NGURAH ALIT SUSANTA WIRYA; I WAYAN DIKSA GARGITA; I KADEK WISMA YUDHA; IDA AYU PUTRI DARMAWATI; YUYUN FITRIANI; I MADE ARIMBAWA; DEWA GEDE WIRYANGGA SELANGGA; RINDANG DWIYANI; NOR KARTINI ABU BAKAR; YUSMIN MOHD-YUSUF (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sudiarta IP, Sanjaya DAPK, Dinarkaya SM, Wirya GNAS, Gargita IWD, Yudha IKW, Darmawati IAP, Fitriani Y, Arimbawa IM, Selangga DGW, Dwiyani R, Bakar NKA, Mohd-Yusuf Y. 2025. First record and potential biocontrol implication of Beauveria bassiana infecting Lema yerburyi on Vanda tricolor from Bali, Indonesia. Biodiversitas 26: 5755-5762. The application of the entomopathogenic fungus Beauveria sp. for biological control has emerged as a viable solution to the problem of excessive insecticide application. Morphological and molecular identification targeting the amplification range of 500-600 bp for entomopathogenic fungal rDNA and 700 bp for insect COI. Pathogenic tests through Koch's postulates, isolated and cultured using Potato Sucrose Agar (PSA) media. The results of the identification of the orchid beetle were identified as Lema yerburyi, and the common name "Orchid lema" was proposed to distinguish it from other orchid beetle pests. Macroscopic identification showed that the isolate Beauveria sp. has a white colony color, with a pale-yellow underside, aseptate hyphae and conidia, with conidia arranged in chains on conidiophores that show a zigzag pattern. Molecular analysis of Beauveria sp. isolates targeting the Internal Transcribed Spacer (ITS) region produced a DNA fragment of ~577 bp. Phylogenetic tree construction showed that this isolate grouped with B. bassiana from Malaysia. This study aimed to identify and confirm the entomopathogenic fungus naturally infecting L. yerburyi in Bali, and to evaluate its potential as a biological control agent. This finding expands the known host range of B. bassiana and provides a scientific basis for its potential application in Integrated Pest Management (IPM) programs for orchids. Future studies should evaluate field efficacy, optimize formulation, and assess its compatibility with existing cultural and biological practices to advance sustainable orchid production.